SUCRALFATE IN THE TREATMENT OF DUODENAL ULCER AND THE EFFECTS ON HELICOBACTER PLORI - A. Reşit BEYLER; Şükrü DUMLU; A. ERTEN; Ali ÖZDEN; Özden UZUNALİMOĞLU (Turkish Journal of Gastroenterology, 2020)
-